Integrated circuits based on broadband pixel-array metasurfaces for generating data-carrying optical and THz orbital angular momentum beams - Willner Alan E.; Su Xinzhou; Song Hao; Zhou Huibin; Zou Kaiheng (Nanophotonics)
There is growing interest in using multiple multiplexed orthogonal orbital angular momentum (OAM) beams to increase the data capacity of communication systems in different frequency ranges. To help enable future deployment of OAM-based communications, an ecosystem of compact and cost-effective OAM generators and detectors is likely to play an important role. Desired features of such integrated circuits include generating and detecting multiple coaxial OAM beams, tunability of OAM orders, and operation over a wide bandwidth. In this article, we discuss the use of pixel-array–based metasurfaces as OAM transmitters and receivers for mode division multiplexing (MDM) communications in near-infrared (NIR) and terahertz (THz) regimes.